PRIORITY ASPECTS OF DEVELOPING THE GREEN ECONOMY IN UZBEKISTAN - Zafar Kh. Rustamov (Ecomind Press, 2025)
This article analyzes the significance of the green economy in Uzbekistan, its development directions, and the ongoing reforms in this area. The author emphasizes sustainable development, environmental safety, and energy efficiency, highlighting the role of the green economy in the national development process.
Keywords: Green economy, sustainable development, technological modernization, environmental sustainability, renewable energy, energy efficiency, waste management, environmental policy.